Perancangan Alat Peleleh Cokelat Untuk Industri Rumah Tangga - Nasrullah Nasrullah (Jurnal Teknik Mesin, 2012)
Recently domestic bakery industry melts chocolate blocks by applying conventional method. They heat certain container filled with water and then another container for melting the chocolate block is put in that container. This process consumes lots of time and money. Therefore, it is necessary to create a tool which can accelerate chocolate melting time, work efficiently and save more time. A device for melting the chocolate can be used to store 4,5 liter of capacity. The mechanism of heating process is based on changing electrical energy to heat with by applying heating element in which the heat will be adjusted by controlling device so the chocolate in the container will melt properly. After the chocolate melts, cooker can adjust the flow of melted chocolate in assigned channel. Allocated time for this melting process depends on the capacity of chocolate inserted in the container and adjustment of heating temperature in the controlling device.